PENGARUH PENDIDIKAN, PENGANGGURAN DAN INFLASI TERHADAP TINGKAT KEMISKINAN DI KAWASAN TIMUR INDONESIA (KTI) PERIODE 2001-2010 - Amalia, Fitri (Jurnal Ilmiah Econosains, 2017)
ABSTRACT This study aims to determine the effect of education, unemployment and inflation on the level of poverty in Eastern Indonesia (KTI) in the period 2001- 2010 . This study uses a sampling techniques to sample the three provinces in Eastern Indonesia, the East Nusa Tenggara, South Sulawesi and Papua. The data used are secondary data is supported by the data panel, the combined time series and cross section data. The analysis shows that the unemployment variable does not affect the level of poverty in Eastern Indonesia. While the other two variables, namely education and inflation have a significant effect with 95% confidence level of the poverty level. Based on F test statistic, showed all the independent variables (education, unemployment and inflation) simultaneously had no significant effect on the level of poverty in Eastern Indonesia at 95% confidence level. Keyword: education, unemployment, inflation, level of poverty